The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fchem.2020.628813
|View full text |Cite
|
Sign up to set email alerts
|

SmBa1-xCaxCo2O5+d Layered Perovskite Cathodes for Intermediate Temperature-operating Solid Oxide Fuel Cells

Abstract: In SmBa1-xCaxCo2O5+d (x = 0.01, 0.03, 0.1, and 0.2, SBCCO) oxide systems calcined at 1100°C for 8 h, the XRD patterns of the SBCCO single phase were maintained in the cases of SmBa0.97Ca0.03Co2O5+d (SBCCO-0.97) and SmBa0.99Ca0.01Co2O5+d (SBCCO-0.99) compositions. In SmBa0.8Ca0.2Co2O5+d (SBCCO-0.8) and SmBa0.9Ca0.1Co2O5+d (SBCCO-0.9), CaCoSmO4 existed with the pattern SBCCO. SBCCO structures were identified as orthorhombic crystal structures because they showed splitting of the X-ray diffraction (XRD) peaks at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For the SOFC technology to be economically viable, reduction in the manufacturing cost of cell components and selectivity of suitable materials for low-temperature operating conditions are vital. In the recent past, noticeable progress has been made in the development of thinner electrolytic membranes 8,9 and vibrant active electrode materials 10,11 that lowered the operating temperature window of SOFC to ∼ 400-800 • C. Perhaps, most of the reported manufacturing techniques for these electrodes preparation engage high-cost equipment, which also involves longer time periods to adjust the processing parameters. 12,13 Ni-GDC cermet has been categorized by numerous investigations as an efficient anodic material for MT-SOFC, Ni-GDC cermet excelled with its superior oxidation of H 2 and better structural stability at intermediate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For the SOFC technology to be economically viable, reduction in the manufacturing cost of cell components and selectivity of suitable materials for low-temperature operating conditions are vital. In the recent past, noticeable progress has been made in the development of thinner electrolytic membranes 8,9 and vibrant active electrode materials 10,11 that lowered the operating temperature window of SOFC to ∼ 400-800 • C. Perhaps, most of the reported manufacturing techniques for these electrodes preparation engage high-cost equipment, which also involves longer time periods to adjust the processing parameters. 12,13 Ni-GDC cermet has been categorized by numerous investigations as an efficient anodic material for MT-SOFC, Ni-GDC cermet excelled with its superior oxidation of H 2 and better structural stability at intermediate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite and its structural variants are utilized as high-performance cathodes for IT-SOFC. Cobaltite which has excellent electrochemical properties, has been studied as a cathode material for IT-SOFCs [6,7]. Double perovskites are suitable as IT-SOFC cathode materials, which require greater surface exchange kinetics and faster oxygen diffusion rates in a moderate temperature range [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, when various materials are substituted, dislocations according to the coulomb potential and elastic potential act on the cathode lattice due to disorder, preventing oxygen ion movement [18]. To solve these problems, many researchers have focused on the development of layered perovskites having a chemical composition of AA / B2O5+d (A: lanthanide Ln, A / : Ba or Sr, B: Co) as cathode materials for SOFCs [20][21][22][23][24][25][26][27]. In layered perovskite, specific crystallographic characteristics have been reported in the case of Ba substituted for the A-site.…”
Section: Introductionmentioning
confidence: 99%
“…Table1summarizes the characteristics of the LnBaCo2O5+d composition of layered perovskite cathode materials. Many research groups reported that the cathode of SOFCs show excellent electrochemical properties whenever the cathode material displays high electrical conductivity[20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%